Climate Politics in Green Deals: Exposing the Political Frontiers of the European Green Deal - Samper, Juan Antonio (2021)
This article investigates the political attempts to frame European climate politics and provides a critical discourse analysis of the European Green Deal. A rapid transition towards low-carbon development across the world has been contested by discourses aiming to acknowledge the inseparability of social and ecological issues. These discussions are fairly new in the European context and in 2019, the European Commission presented its Communication on the European Green Deal—the European Union’s legislative roadmap to carbon neutrality by 2050. Empirical evidence for this article is derived from process tracing and policy analysis of the European Commission’s documents on the European Green Deal in relation to existing Green New Deals. Drawing from a neo-Gramscian perspective we argue that the European Green Deal is an attempt to extend the neoliberal hegemonic formation within European climate politics. This results in the foreclosure of democratic channels for articulating climate politics according to dissenting discourses, thereby avoiding the political contestation inherent to climate politics.